HUMAN CAPITAL IS A CORE VALUE DIGITAL ECONOMY - Sherzod Dekhkanov (Scholar Express Journals, 2022)
This article reveals the formation of the spread and development of human capital, its cardinal transformation, which are necessary both for participation in the creation and dissemination of digital technologies, and for their use in the business process in the digital world of knowledge, skills and determining factors of production, entrepreneurship and employment. The article substantiates and recommends the competence model and its indicators in the Fergana region.
Keywords: digital technologies, digital transformation, digital literacy, digital competence, digital consumption, digital security, digital communication, competence model, formation, human capital, project implementation